The information asymmetry and the consumer of technological products in the internet era - Huarag Guerrero, Enrico Marcel (2021)
The acquisition of technological products confronts consumers with a phenomenon of deep information asymmetry. To adopt an efficient consumption decision, abundant and complex information is required. Consumer protection agencies often transfer the obligation to provide this information to the provider. However, due to the quantity, variety and complexity of the information required, this would only make the final price of the product more expensive, without being useful for all consumers. On the other hand, the information supplied by the provider is always suspicious, because what they are looking for is to sell the product. The internet provides consumers with enough tools to get all the necessary information, not only from providers, but also from third parties. Third parties have incentives to produce truthful, objective, and impartial information, much more useful to the consumer than what the provider could provide.